Quantum Learning Method Strategy in Maharah Kalam Learning Activities in Aidina Classroom of Students Ocean Arabic Pare Kediri - Mhd Ibnu Hanan Al Faruqi; M Faisol; Idrus Muchsin Bin Agil; Zulfa Al Muthoharoh; Surya Hidayat (al-Afkar, Journal For Islamic Studies, 2026)
Learning maharah kalam (speaking skills) in Arabic requires methods that are able to create a fun, interactive, and able to arouse students' enthusiasm to actively communicate. This study aims to describe the strategy of applying the Quantum Learning method in maharah kalam learning activities in the Aidina Class, Ocean Arabic Pare Kediri Students. This study uses a descriptive qualitative approach, with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that the Quantum Learning strategy is applied through several stages such as Prime, Experience, Label, Demonstrate, Review, and Celebrate. This strategy creates fun learning, increases students' confidence in speaking Arabic, and makes the learning process more meaningful. However, several challenges are still faced, such as the need for teachers' creativity and the limitations of learning media.